GAMBARAN OHI-S DAN PERILAKU MENYIKAT GIGI PADA REMAJA PEROKOK DI BANJAR TENGAHDESA KUKUH KECAMATAN MARGA KABUPATEN TABANAN TAHUN 2017 - Ni Made Sirat; Sagung Agung Putri Dwiastuti; I G A A Dharmawati; Gusti Ayu Ari Purnamadewi (Jurnal Kesehatan Gigi (Dental Health Journal), 2020)
Oral Hygiene is a free conditions of teeth from plaque and calculus. Oral health is influenced by several factors, one of which factor is regularity of brushing teeth. The purpose of this research is to know OHI-Sdescription and brushing teeth behavior of smoker teenagers in Banjar Tengah, Kukuh village, Marga sub districts, Tabanan regency, 2017. This research is a descriptive are using the total population about 35 smoker teenagers. The result of this research is smoker teenagers with OHI-S good criterias four peoples, 19 peoples includes moderate criteria, and bad criteria seven peoples. The average of smoker teenagers OHI-S is 2,45 with a moderate criteria. Smoker teenagers who behave that teeth brushing behavior with a very good criteria one people, four peoples good criteria, the criteria quite seven peoples, and 32 peoples with need guidance criteria. Based on the results of the study it can be concluded smoker teenagers have a highest OHI-S medium criteria, the average OHI-S 2,45 and the most brushing teeth behavior that need guidance criteria. Suggestion can be given that should  do counseling about how to maintain oral health and counseling about danger and smoking consequence in order to create a good health status.